Solomon's code : humanity in a world of thinking machines - Groth, Olaf; Nitzberg, M. (Mark), 1961-; Zehr, Dan (Pegasus Books, 2018)
Whether in medicine, money, or love, technologies powered by forms of artificial intelligence are playing an increasingly prominent role in our lives. As we cede more decisions to thinking machines, we face new questions about staying safe, keeping a job and having a say over the direction of our lives. The answers to those questions might depend on your race, gender, age, behavior, or nationality. New AI technologies can drive cars, treat damaged brains and nudge workers to be more productive, but they also can threaten, manipulate, and alienate us from others. They can pit nation against nation, but they also can help the global community tackle some of its greatest challenges<U+2015>from food crises to global climate change. In clear and accessible prose, global trends and strategy adviser Olaf Groth, AI scientist and social entrepreneur Mark Nitzberg, along with seasoned economics reporter Dan Zehr, provide a unique human-focused, global view of humanity in a world of thinking machines.